(untitled) (International Journal of Innovative Technologies in Economy, 2018)
This article studies the development of e-business in the Republic of Kazakhstan. The analysis includes the following moments: most popular forms of e-business in Kazakhstan, current situation, and, finally, the problems and prospects of development.